2018
DOI: 10.1021/acs.chemmater.8b02497
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Tunable Upconversion Luminescence from Sensitized Seed-Mediated Grown LiGdF4:Yb,Tm-Based Core/Triple-Shell Nanophosphors for Transparent Displays

Abstract: Red, green, blue, and natural white upconversion (UC) luminescence colors are realized from the tetragonal-structured LiGdF4-based core/triple-shell (C/T-S) upconversion nanophosphors (UCNPs) and the C/T-S UCNP-incorporated polymer composites. The LiYF4:Yb cores are used as sensitized seeds for the formation of LiGdF4:Yb,Tm UC shell followed by the growth of LiGdF4:Tb,Eu color tuning shell. Finally, LiYF4 inert shell is grown on the core/shell/shell UCNPs, and LiYF4:Yb/LiGdF4:Yb,Tm/LiGdF4:Tb,Eu/LiYF4 C/T-S UCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 51 publications
0
46
0
1
Order By: Relevance
“…Moreover, the lattice mismatch between an undoped LiYF4 shell and the doped LiYF4 core particle is low which reduces the risk of forming defect states at the core-shell interface. Other shell materials were nevertheless also investigated such as LiGdF4 [65,69], LiLuF4 [71], LiYbF4 [73], SiO2 [63,80], doped LiYF4 [76,77] as well as more complicated particle architectures involving multiple shells [69,74].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lattice mismatch between an undoped LiYF4 shell and the doped LiYF4 core particle is low which reduces the risk of forming defect states at the core-shell interface. Other shell materials were nevertheless also investigated such as LiGdF4 [65,69], LiLuF4 [71], LiYbF4 [73], SiO2 [63,80], doped LiYF4 [76,77] as well as more complicated particle architectures involving multiple shells [69,74].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, fluoride anions engage in fluorination and cleave Gd-OOCCF 3 bonds to promote nucleation, and the thus obtained crystal nuclei agglomerate to form larger particles as the reaction progresses. With the increase of temperature, the growth rate of these nuclei crystal nucleus increases and eventually forms nanocrystals [45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the gadolinium network‐mediated energy migration strategy to tune the UC characteristics of CSX structures relies on a five‐photon process whose efficiency as a function of the excitation power density has rarely been reported through the measurement of the corresponding absolute UCQY. As far as it is known, only recently Shin et al have reported the absolute UCQY for LiYF 4 :Yb/LiGdF 4 :Yb:Tm/LiGdF 4 :Tb:Eu/LiYF 4 (tetragonal phase) ranging from 1.1% to 2.5% at 106 W cm −2 …”
Section: Core–shell Upconverting Architecturesmentioning
confidence: 99%